BUDGETARY CONSTRAINTS ON JUDICIAL INDEPENDENCE IN WESTERN BALKAN COUNTRIES - Shapkova Kocevska, Katerina (My University, 2019)
Independent and impartial judicial systems do not exist without financial independence. Financial stability and transparent and objective resource mobilization and allocation in the judiciary are expected to strengthen courts’ performance, limit pressure from different sources on judges’ ruling, discourage corruptive behavior or practices and improve judges’ integrity. Ultimately, these processes result in wider legal, political and economic advantages, including ensuring rule of law, strengthening democratic capacities and improving formal institutions relevant to the economic environment. The purpose of this paper is to analyze and compare the budgetary constraints to the judicial system in five Western Balkans countries, including Albania, Bosnia and Herzegovina, Montenegro, North Macedonia, and Serbia in the period from 2010 to 2016. The comparative analysis of the different variables used as proxies of budgetary constraints has shown that Montenegro has the best performance with regard to allocating resources towards the judiciary system. However, all of the analyzed countries lag significantly behind the European average, which indicates the existence of an urgent need for improvements in resource allocation and mobilization in the judiciary systems in the Western Balkans region.
Keywords: Key words: court independence; court impartiality; financial independence; court budget; prosecution services budget; Western Balkans.